Preparation method of reinforced titanium-based composite materials based on selective laser melting

By using the composite powder distributed in the titanium -based composite material and the three peak distribution of the selection area and the particle size, the problem of insufficient hardness and abrasion resistance of titanium -based composite materials is solved, and the high hardness and good mechanics of titanium -based composite materials are enhanced. Performance, suitable for metal parts that manufacture complex structures.

CN116144965BActive Publication Date: 2025-01-28KUNMING UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310166665.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-27
Publication Date
2025-01-28
Estimated Expiration
2043-02-27

AI Technical Summary

Technical Problem

The existing titanium-based composite materials have shortcomings in hardness and wear resistance, and it is difficult for traditional preparation processes to manufacture parts with complex structures.

Method used

The preparation method based on the laser melting of the constituency is used to make the nano TIB2 and micron TIB2 powder with Ti6AL4V powder for ball milling treatment to form a composite powder distributed in three peaks.

Benefits of technology

The generated TIBW is evenly distributed in the TI matrix, and has a variety of long -diameter ratio mixed cases. It forms a macro uniform and micro -mixed mesh structure, which significantly improves the hardness and mechanical properties of titanium -based composite materials. Component.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116144965B_ABST
    Figure CN116144965B_ABST
Patent Text Reader

Abstract

The present application provides a method for preparing a reinforced titanium-based composite material based on selective laser melting, comprising the steps of: S1, preparing composite powder: adding nano-TiB2 powder, micron TiB2 powder and Ti6Al4V powder into a ball mill and subjecting them to ball milling treatment under an argon atmosphere to obtain a uniformly mixed composite powder; S2, SLM forming: using the composite powder obtained in S1 for an SLM forming process to obtain a block sample. The advantages of the present invention are that the TiBw generated in the prepared reinforced titanium-based composite material is uniformly distributed in the Ti matrix, and TiBw also exhibits a variety of aspect ratios. Its macro-uniform and micro-mixed reticular structure is conducive to inhibiting deformation and crack expansion, so that the hardness of the prepared titanium-based composite material is significantly improved, and it has good density and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of additive manufacturing, and in particular to a preparation method and equipment for a reinforced titanium-based composite material based on selective laser melting. Background Art

[0002] Titanium alloys have good mechanical properties, excellent corrosion resistance and high biocompatibility, and have been widely used in biomedicine, aerospace and automotive industries. However, titanium alloys have low hardness and poor wear resistance, which leads to certain limitations in their application in the above fields. Titanium-based composites are a type of composite material that uses titanium or titanium alloy as a matrix and is obtained by in-situ generation of reinforcing phases. They have a series of advantages such as high strength and good wear resistance. TiB whiskers have the advantages of high chemical stability, high hardness, high wear resistance, etc., and are considered to be one of the most ideal reinforcements in titanium-based composites.

[0003] The performance of titanium-based composites is also affected by the preparation process. The main methods for preparing titanium-based composites are traditionally powder metallurgy, casting, reactive hot pressing and other process technologies. However, these process technologies have limitations that cannot be ignored, the most typical of which is that it is difficult to manufacture parts with complex structures. The selective laser melting (SLM) process can achieve high-degree-of-freedom near-net forming of complex parts without the need for molds. At present, there are few studies on the use of SLM to strengthen titanium-based composites, and the precursor TiB2 powder used for the reaction to generate TiBw is of a single particle size, and the strengthening effect is not ideal.

[0004] For example, Cai et al. used TiB2 powder with an average particle size of 2.71 μm and successfully prepared TiB / Ti6Al4V composite materials by SLM. Compared with the Ti6Al4V alloy prepared by SLM, the hardness and wear resistance of the composite material were improved. However, the TiBw distribution in the composite material was uneven, enriched in some areas and less in other areas (In-situ preparation and formation of TiB / Ti6Al4V nanocomposite via laser additive manufacturing: Microstructure evolution and tribological behavior, Powder Technology 342 (2019) 73-84). Zhou et al. used TiB2 powder with a particle size of 100-200 nm to prepare TiB / Ti6Al4V composites by SLM, and the tensile strength of the composites was as high as 1775 MPa. However, the TiBw in the composite material was only a quasi-continuous structure with a relatively simple morphology (Microstructure evolution and mechanical properties of in-situ Ti6Al4V-TiB composites manufactured by selective laser melting, Composites Part B: Engineering 207 (2021) 108567). Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a method for preparing a reinforced titanium-based composite material based on selective laser melting. The TiBw generated in the prepared reinforced titanium-based composite material is evenly distributed in the Ti matrix, and TiBw also exhibits a variety of aspect ratios. Its macroscopically uniform and microscopically mixed network structure is beneficial to inhibiting deformation and crack propagation, so that the hardness of the prepared titanium-based composite material is significantly improved, and it has good density and mechanical properties.

[0006] The present invention provides a method for preparing a reinforced titanium-based composite material based on selective laser melting, comprising the following steps:

[0007] S1. preparing composite powder: adding nano-TiB2 powder, micron-TiB2 powder and Ti6Al4V powder into a ball mill and performing ball milling treatment under an argon atmosphere to obtain a uniformly mixed composite powder;

[0008] S2, SLM forming: The composite powder obtained in S1 is placed in a selective laser melting device. The powder spreading device spreads the composite powder on a forming substrate. The composite powder is melted layer by layer by laser, and a block sample is obtained after solidification.

[0009] Preferably, the mass fractions of the components of the composite powder in step S1 are: 1.2-3.2% for nano-TiB2 powder, 1.8-4.8% for micron-TiB2 powder, and 92-97% for Ti6Al4V powder.

[0010] Preferably, the average particle size of the nano-TiB2 powder in step S1 is 100-200 nm, the average particle size of the micron TiB2 powder is 1-5 μm, and the average particle size of the Ti6Al4V powder is 15-53 μm.

[0011] Preferably, in step S2, the composite powder is first subjected to vacuum drying treatment before being placed in the selective laser melting equipment.

[0012] Preferably, the ball mill speed in step S1 is 100-200 rpm, and the ball milling time is 1-3 hours.

[0013] Preferably, the vacuum drying temperature in step S2 is 60 to 90° C., and the drying time is 8 to 10 hours.

[0014] Preferably, the process parameters of SLM forming in step S2 are: laser power 50-350 W, scanning speed 200-600 mm / s, scanning spacing 60-100 μm, powder layer thickness 30-60 μm, and substrate preheating temperature 120-180°C.

[0015] Preferably, after step S2, the method further comprises S3, obtaining a reinforced titanium-based composite material: cutting the prepared block sample from the substrate to obtain a reinforced titanium-based composite material.

[0016] The present invention has the following beneficial effects:

[0017] (1) Compared with TiB2 powder with a single particle size, the use of TiB2 with nanometer and micrometer particle sizes as precursors for in-situ reaction with Ti not only makes the generated TiBw evenly distributed in the Ti matrix, but also TiBw exhibits a mixed state of multiple aspect ratios. Its macroscopically uniform and microscopically mixed network structure is conducive to inhibiting deformation and crack propagation, significantly improving the hardness of the prepared titanium-based composite material, and having good density and mechanical properties.

[0018] (2) The present invention uses a TiB2 / Ti6Al4V composite powder with a trimodal particle size distribution, wherein the sphericity of the Ti6Al4V powder is well maintained, nano-sized TiB2 is attached to the Ti6Al4V, and micron-sized TiB2 is evenly distributed around the Ti6Al4V powder and can fill the micron-sized gaps between the Ti6Al4V powders. Compared with adding TiB2 powder with a single particle size, the composite powder with a trimodal particle size distribution prepared by the present invention can not only obtain better powder fluidity during the SLM powder spreading process, but also improve the density of the powder spreading layer.

[0019] (3) Compared with traditional mechanical processing methods, the present invention prepares reinforced titanium-based composite materials based on selective laser melting technology, realizes high-degree-of-freedom near-net forming of entities, and is suitable for manufacturing metal parts with complex structures, which can meet the needs of aerospace, automobile, shipbuilding, biomedicine and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The scanning electron microscope morphology comparison diagram of pure Ti6Al4V powder (a) and the composite powder in Example 1 (b);

[0021] Figure 2 Microstructure morphology of SLM formed Ti6Al4V alloy (ab) and reinforced titanium-based composite material prepared in Example 1 (cd). DETAILED DESCRIPTION

[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Example 1

[0024] A method for preparing a reinforced titanium-based composite material based on selective laser melting comprises the following steps:

[0025] S1. Preparation of composite powder: Add nano-TiB2 powder, micron-TiB2 powder and Ti6Al4V powder into a ball mill and perform ball milling under argon atmosphere to obtain a uniformly mixed composite powder; the ball mill speed is 100 rpm, and the ball milling time is 3 hours; the mass fractions of the components of the composite powder are: nano-TiB2 powder 1.2%, micron-TiB2 powder 1.8%, Ti6Al4V powder 97%; the average particle size of the nano-TiB2 powder is 100 nm, the average particle size of the micron-TiB2 powder is 1 μm, and the average particle size of the Ti6Al4V powder is 15 μm.

[0026] S2, SLM forming: the composite powder obtained in S1 is vacuum dried and then placed in a selective laser melting device. The powder spreading device spreads the composite powder on a forming substrate, and the composite powder is melted layer by layer by laser to obtain a block sample after solidification. The vacuum drying temperature is 60°C and the drying time is 10 hours. The process parameters of SLM forming are: laser power 200W, scanning speed 400mm / s, scanning spacing 100μm, powder layer thickness 60μm, and substrate preheating temperature 150°C.

[0027] S3. Obtaining a reinforced titanium-based composite material: cutting the prepared block sample from the substrate to obtain a reinforced titanium-based composite material.

[0028] Figure 1 The scanning electron microscope morphology comparison diagram of pure Ti6Al4V powder (a) and composite powder (b) in Example 1. It can be seen that in the composite powder with trimodal particle size distribution in this embodiment, the sphericity of Ti6Al4V powder is well maintained, nano-sized TiB2 is attached to Ti6Al4V, micron-sized TiB2 is evenly distributed around Ti6Al4V powder, and can fill the micron-sized gaps between Ti6Al4V powders. Compared with adding TiB2 powder with a single particle size, the composite powder with trimodal particle size distribution in this embodiment can not only obtain better powder fluidity during the SLM powder spreading process, but also improve the density of the powder spreading layer.

[0029] Figure 2 The microstructure morphology of the SLM-formed Ti6Al4V alloy (ab) and the reinforced titanium-based composite material (cd) prepared in Example 1. It can be seen that compared with the simple SLM-formed Ti6Al4V alloy, the use of TiB2 with nanometer and micrometer particle sizes as precursors for in-situ reaction with Ti not only makes the generated TiBw evenly distributed in the Ti matrix, but also TiBw also shows a variety of aspect ratios. Its macro-uniform and micro-mixed network structure is conducive to inhibiting deformation and crack expansion, significantly improving the hardness of the prepared titanium-based composite material, and having good density and mechanical properties.

[0030] Example 2

[0031] A method for preparing a reinforced titanium-based composite material based on selective laser melting comprises the following steps:

[0032] S1. Preparation of composite powder: Add nano-TiB2 powder, micron-TiB2 powder and Ti6Al4V powder into a ball mill and perform ball milling under argon atmosphere to obtain a uniformly mixed composite powder; the ball mill speed is 150 rpm, and the ball milling time is 2 hours; the mass fractions of the components of the composite powder are: nano-TiB2 powder 1.8%, micron-TiB2 powder 2.6%, Ti6Al4V powder 95.6%; the average particle size of nano-TiB2 powder is 150 nm, the average particle size of micron-TiB2 powder is 3 μm, and the average particle size of Ti6Al4V powder is 34 μm.

[0033] S2, SLM forming: The composite powder obtained in S1 is vacuum dried and then placed in a selective laser melting device. The powder spreading device spreads the composite powder on a forming substrate, and the composite powder is melted layer by layer by laser to obtain a block sample after solidification. The vacuum drying temperature is 75°C and the drying time is 9 hours. The process parameters of SLM forming are: laser power 275W, scanning speed 400mm / s, scanning spacing 100μm, powder layer thickness 60μm, and substrate preheating temperature 150°C.

[0034] S3. Obtaining a reinforced titanium-based composite material: cutting the prepared block sample from the substrate to obtain a reinforced titanium-based composite material.

[0035] Example 3

[0036] A method for preparing a reinforced titanium-based composite material based on selective laser melting comprises the following steps:

[0037] S1. Preparation of composite powder: Add nano-TiB2 powder, micron-TiB2 powder and Ti6Al4V powder into a ball mill and perform ball milling under argon atmosphere to obtain a uniformly mixed composite powder; the ball mill speed is 200 rpm, and the ball milling time is 1 hour; the mass fractions of the components of the composite powder are: nano-TiB2 powder 3.2%, micron-TiB2 powder 4.8%, Ti6Al4V powder 92%; the average particle size of the nano-TiB2 powder is 200 nm, the average particle size of the micron-TiB2 powder is 5 μm, and the average particle size of the Ti6Al4V powder is 53 μm.

[0038] S2, SLM forming: the composite powder obtained in S1 is vacuum dried and then placed in a selective laser melting device. The powder spreading device spreads the composite powder on a forming substrate, and the composite powder is melted layer by layer by laser to obtain a block sample after solidification. The vacuum drying temperature is 690°C and the drying time is 8 hours. The process parameters of SLM forming are: laser power 350W, scanning speed 400mm / s, scanning spacing 100μm, powder layer thickness 60μm, and substrate preheating temperature 150°C.

[0039] S3. Obtaining a reinforced titanium-based composite material: cutting the prepared block sample from the substrate to obtain a reinforced titanium-based composite material.

[0040] In order to verify the strengthening effect of the present application, a comparative example was set up: an equal amount of Ti6Al4V powder as the composite powder in Example 3 was taken to replace the composite powder, and the remaining processes and parameters were the same as those in Example 3.

[0041] Test 1: Hardness test

[0042] The samples obtained in Example 1, Example 2, Example 3 and Comparative Example 1 were respectively taken for Vickers microhardness test, and the hardness results are shown in the following table:

[0043] Sample Example 1 Example 2 Example 3 Comparative Example 1 Hardness(Hv) 635.9±6 606.2±9 627.1±10 492.6±10

[0044] It can be seen from the hardness test results that the hardness of the reinforced titanium-based composite material prepared in the present application is significantly enhanced, which can reach more than 600Hv. Compared with ordinary titanium-based composite materials, the hardness is increased by more than 23%.

[0045] Test 2: Dry friction and wear test

[0046] The samples obtained in Example 1, Example 2, Example 3 and Comparative Example 1 were respectively taken to carry out dry friction and wear tests, and the measured COF results are shown in the following table:

[0047] Sample Example 1 Example 2 Example 3 Comparative Example 1 COF 0.45 0.51 0.47 0.55

[0048] It can be seen from the COF test results that the friction coefficient of the reinforced titanium-based composite material prepared in the present application is lower than that of the ordinary titanium-based composite material, and the wear resistance is improved.

[0049] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.

Claims

1. A method for preparing a reinforced titanium-based composite material based on selective laser melting, characterized in that: The steps include: S1. Preparation of composite powder: adding nano-TiB2 powder, micron-TiB2 powder and Ti6Al4V powder into a ball mill and performing ball milling treatment under an argon atmosphere to obtain a uniformly mixed composite powder; S2, SLM forming: The composite powder obtained in S1 is placed in a selective laser melting device. The powder spreading device spreads the composite powder on a forming substrate. The composite powder is melted layer by layer by laser, and a block sample is obtained after solidification.

2. The method for preparing a reinforced titanium-based composite material based on selective laser melting according to claim 1, characterized in that: The mass fractions of the components of the composite powder in step S1 are: 1.2-3.2% of nano-TiB2 powder, 1.8-4.8% of micron-TiB2 powder, and 92-97% of Ti6Al4V powder.

3. The method for preparing a reinforced titanium-based composite material based on selective laser melting according to claim 2, characterized in that: The average particle size of the nano-TiB2 powder in step S1 is 100-200 nm, the average particle size of the micron TiB2 powder is 1-5 μm, and the average particle size of the Ti6Al4V powder is 15-53 μm.

4. The method for preparing a reinforced titanium-based composite material based on selective laser melting according to claim 1, characterized in that: The ball mill speed in step S1 is 100-200 rpm, and the ball milling time is 1-3 hours.

5. The method for preparing a reinforced titanium-based composite material based on selective laser melting according to claim 1, characterized in that: In step S2, the composite powder is first subjected to vacuum drying treatment before being placed in the selective laser melting equipment.

6. The method for preparing a reinforced titanium-based composite material based on selective laser melting according to claim 5, characterized in that: The vacuum drying temperature is 60 to 90° C., and the drying time is 8 to 10 hours.

7. The method for preparing a reinforced titanium-based composite material based on selective laser melting according to claim 1, characterized in that: The process parameters of SLM forming in step S2 are: laser power 50-350 W, scanning speed 200-600 mm / s, scanning spacing 60-100 μm, powder layer thickness 30-60 μm, and substrate preheating temperature 120-180 °C.

8. The method for preparing a reinforced titanium-based composite material based on selective laser melting according to claim 1, characterized in that: The method further comprises S3 after step S2, obtaining a reinforced titanium-based composite material: cutting the prepared block sample from the substrate to obtain a reinforced titanium-based composite material.

Citation Information

Patent Citations

  • Nano-particle reinforced titanium-based composite material based on SLM forming and preparation method thereof

    CN113215441A